Weed Management in Corn - Jason A. Ferrell; Gregory E. MacDonald; Pratap Devkota (EDIS)
Successful weed control is essential for economical corn production in Florida. Weeds reduce corn yields by competing for moisture, nutrients, and light during the growing season and interfere with harvest. Producing a good corn crop is only half the battle and will not be profitable unless the corn can be harvested. Late-season weeds can result in excessive yield loss, inefficient equipment operation, and provide a source of weed seed for the following season. Weeds can be controlled in corn; however, this involves good management practices in all phases of corn production. https://edis.ifas.ufl.edu/wg007